The effectiveness of web-based interventions on non-alcoholic fatty liver disease (NAFLD) in obese children: A study protocol for a randomized controlled trial - Tian, Caixia; Xu, Jinliang; Wang, Guofen; Yu, Lidi; Tang, Xiaoli (Frontiers in Public Health, 2022)
Aim Nonalcoholic fatty liver disease (NAFLD) is currently the most prevalent liver disease in the world, increasing the risk of cirrhosis and hepatocellular carcinoma, and contributing to the development of type 2 diabetes, cardiovascular disease, and chronic kidney disease. This study aims to carry out a web-based continuum of a care intervention model to provide comprehensive care interventions for obese children with NAFLD, to improve the effectiveness of treatment of children with NAFLD. Design A 1-year single-blinded randomized clinical trial in hospital in Zhejiang Province. Methods Eighty subjects will implement the program in a randomized order. The interventions for the control group mainly consisted of the routine distribution of health education materials and health education by holding health-themed lectures, and the preliminary proposed interventions including establishing management teams, regularly delivering related health knowledge, daily uploading of health intervention records, regular supervision and mutual encouragement, home visiting and psychological guidance. The primary outcomes are serum biomarkers such as alanine aminotransferase (ALT) and gamma-glutamyl transferase (GGT), aspartate aminotransferase, and imaging (liver ultrasound and magnetic resonance imaging). Second outcomes are: BMI，waist-to-hip ratio and quality of life. In addition, socio-demographic characteristics such as age, gender and ethnicity will be recorded. Children aged 7-18 years old and diagnosed with NAFLD will be included, patients will be not eligible if they do not agree to participate or are participating in other health intervention programs. This study was registered on ClinicalTrials.gov (NCT05527938). Results Over the past 30 years, NAFLD has been recognized as one of the most common liver diseases in adults and children. The current studies have focused on promoting lifestyle changes in children with NASH by providing some education and advice to children and their families to improve the histological features of NASH and lose weight. Because of the convenience and efficiency of the internet can provide some new strategies and ways for lifestyle interventions for children with NAFLD. In addition, we have designed a high-quality RCT based on the SPIRIT guidelines, which also provides strong evidence in this area.